Exploratory study on the training of science teachers in an interdisciplinary approach: case of training in health sciences at the higher institute of nursing and health techniques. - KHOAJA, Driss; DAAIF, Jabran; LAMIRI, Abderrahmane; HORR, Latifa; RAOUF, Khadija; BELAAOUAD, Said; KHAYATI, Abderrahim (International Journal of Psychosocial Rehabilitation, 2024)
In order to enrich the training of science teachers, who require a diversity of knowledge and a broad field of vision on several disciplines taught, we are studying the application of the interdisciplinary approach that could be a solution to the training program. For it "allows for the integration of several types of knowledge and skills, in the sense of helping to keep up with the evolution of knowledge and improve the teaching method, while promoting meaningful learning based on authentic situations"(4). In this context, we focus on the study of this interdisciplinary approach among health science teachers at the Higher Institute of Nursing and Health Technology (ISPITS Casablanca), where students are trained to become nursing professionals. Thus, we seek to know if these teachers practice the criteria of the interdisciplinary approach in this training, and if they take into account its added value to teaching. We try to detect if there is a coordination between actors prior to a collaboration between these stakeholders and if there is at the same time an integration of knowledge, which constitutes for us the project of professionalization in action (conceptualization in action) in clinical settings. Thus, to do this, we use the quantitative method by interviewing teachers using a questionnaire adapted and inspired by that of REGE COLET, to investigate the skills they were seeking to develop in real situations among the trainees(9). We are also trying to define this approach and give some insight into its interest in the acquisition of new teaching methods and to approach the paradigm of interdisciplinarity and show the interest there may be in its evaluation tools. Finally, an analysis of the description in relation to a reading grid developed from the pedagogical indicators of the interdisciplinary approach completes our study. The result of the calculation of the interdisciplinarity index of this training (Indid = (organization of knowledge) / (organization of work)) allowed us to deduce that the quality of this training is of a relational interdisciplinarity(9). an analysis of the description in relation to a reading grid developed from the pedagogical indicators of the interdisciplinary approach completes our study. The result of the calculation of the interdisciplinarity index of this training (Indid = (organization of knowledge) / (organization of work)) allowed us to deduce that the quality of this training is of a relational interdisciplinarity (9). an analysis of the description in relation to a reading grid developed from the pedagogical indicators of the interdisciplinary approach 1completes our study. The result of the calculation of the interdisciplinarity index of this training (Indid = (organization of knowledge) / (organization of work)) allowed us to deduce that the quality of this training is of a relational interdisciplinarity (9)